Reporting under extreme conditions: journalists' experience of disaster coverage - Englund, Liselotte; Bergh Johannesson, Kerstin; Arnberg, Filip K. (Frontiers in Communication, 2023)
Introduction Media presence on site and reports on disasters are crucial parts of disaster communication. Aside from authorities, civil society, concerned businesses and citizens, the media constitute an important actor. The working conditions, situational competence and management among journalists on duty in a disaster area are important factors within the complex area of crisis management and disaster communication. This study aims to explore the working conditions, challenges, and coping strategies among journalists covering the Haiti earthquake in 2010. Methods Ten months after the event, Scandinavian journalists (n = 32) provided free-text responses about their work on site through a web survey. The free- text responses underwent content analysis. In addition, self-report questionnaires were used to assess general mental health and posttraumatic stress. Results We found that journalists faced five main challenges in Haiti: situational (technicalities, practical, collegial), professional (mission, approach, roles), personal (traits, emotions, coping), traumatic (general mental health and posttraumatic stress) and experiential (learning and growth). They described a difficult and challenging mission, but also an eye-opening and life-changing experience. Most respondents' questionnaire responses indicated low risk for both poor mental health and posttraumatic stress, with a few significant exceptions. Being properly equipped and mentally prepared, getting collegial support and maintaining professional focus were seen as important, and good leadership and clear instructions from editors at home were highlighted. Discussion Corroboration of the present findings would strengthen our knowledge of their experiences, and may provide valuable insights for designing preparedness activities in the future as well as for applying to other communication functions in disasters.